Advances in teaching–learning-based optimization algorithm: A comprehensive survey(ICIC2022) - Zhou, Guo; Zhou, Yongquan; Deng, Wu; Yin, Shihong; Zhang, Yunhui (Neurocomputing (Amsterdam), 2023)
•Teaching-learning-based optimization (TLBO) is one of population-based heuristic stochastic swarm intelligent algorithm.•In this paper, a comprehensive survey on the recent advances in TLBO is presented.•Literature survey reveals some interesting challenges and future research directions. Teaching-learning-based optimization (TLBO) algorithm which imitates the teaching–learning process in a classroom, is one of population-based heuristic stochastic swarm intelligent algorithms. TLBO executes through similar iterative evolution processes as utilized by a standard evolutionary algorithm. Unlike traditional evolutionary algorithms and swarm intelligent algorithms, the iterative computation process of teaching–learning-based optimization is divided into two phases and each phase executes iterative learning operation. In this paper, we present a comprehensive survey on the recent advances in TLBO. A review of the current literature reveals intriguing challenges and suggests potential future research directions.